2018
DOI: 10.1002/elps.201800039
|View full text |Cite
|
Sign up to set email alerts
|

Study of the enantiomeric separation of the anticholinergic drugs on two immobilized polysaccharide‐based chiral stationary phases by HPLC and the possible chiral recognition mechanisms

Abstract: In this work, the enantiomeric separation of ten anticholinergic drugs was first examined on two derivative polysaccharide chiral stationary phases (CSPs), i.e., Chiralpak ID and Chiralpak IA in the normal phase mode. Except for scopolamine hydrobromide, the remaining nine analytes could be completely separated with good resolutions using both columns under the optimized mobile phase conditions. And the enantiomeric discrimination ability of the studied CSPs towards nine analytes was in the order of Chiralpak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…As a consequence of the negative values for Δ H °, Δ S *, Δ G °, the solute transfer from the mobile to stationary phase was enthalpically favorable but entropically unfavorable in this temperature range. Additionally, the Van't Hoff plots for the retention (ln k versus 1/ T ) of all racemates were linear with coefficient of determination ( r 2 ) ranging from 0.9810 to 0.9990, suggesting that the retention mechanism was independent of temperature in the studied range .…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…As a consequence of the negative values for Δ H °, Δ S *, Δ G °, the solute transfer from the mobile to stationary phase was enthalpically favorable but entropically unfavorable in this temperature range. Additionally, the Van't Hoff plots for the retention (ln k versus 1/ T ) of all racemates were linear with coefficient of determination ( r 2 ) ranging from 0.9810 to 0.9990, suggesting that the retention mechanism was independent of temperature in the studied range .…”
Section: Resultsmentioning
confidence: 85%
“…The related thermodynamic parameters were calculated by Van't Hoff equations : ΔG=ΔHTΔSleft ln k0.16emleft=left0.16emnormalΔH/0ptnormalΔH RT 0.0pt RT 0.16em+0.16emnormalΔS/0ptnormalΔSR0.0ptR0.16em+0.16em ln normalΦleftleft=0.16emnormalΔH/0ptnormalΔH RT 0.0pt RT 0.16em+0.16emnormalΔS/0ptnormalΔSR0.0ptRwhere ΔG°, ΔH°, and ΔS° represent the standard Gibbs free energy, enthalpy, and entropy of solute transfer from the mobile phase to the CSP, T is the absolute temperature, and R is the gas constant (8.314 J/mol/K). Since the value of Φ is unknown, the Δ S * value [Δ S * = Δ S °+ R ln Φ] is generally used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Column temperature is regarded as a significant parameter with reference to chiral separations . The thermodynamic parameters could be calculated according to the capacity factor (k), separation factor (α), and resolution (Rs) by classical Van't Hoff equations, which assumes that analyte retention is only due to enantioselective interactions with the stationary phase and does not distinguish between chiral and nonchiral interactions . The classical Van't Hoff equations are exhibited as follows: lnk=normalΔH°RT+normalΔS°R+lnnormalΦ=normalΔH°RT+normalΔS*R, lnα=ΔΔH°RT+ΔΔS°R. …”
Section: Resultsmentioning
confidence: 99%
“…The negative Δ H ° values revealed that the distribution of the two enantiomers between the mobile phase and the stationary phase was exothermic. Moreover, both ΔΔ H ° and ΔΔ S ° were negative showing that separation of flumequine was enthalpy‐driven …”
Section: Resultsmentioning
confidence: 99%